An analysis of the technical efficiency of small-scale cacao farmers in Calinan, Davao City - Gonzaga, Mae Liza T.
Philippine cacao has earned acceptance in the local and in the international market because of its comparative advantage in producing well-fermented cacao than other neighboring cacao-producing countries in Asia. In addition, the low cost of importation of cacao in the country makes it favorable for the international market to import cacao from the Philippines. However, despite the surging demand for Philippine cacao beans, the domestic production remained low and could not lessen the gap between supply and demand. In order to find out the sources of inefficiency, personal interviews were conducted from 150 small-scale cacao farmers from eight different barangays in Calinan District, Davao City. Stochastic Frontier Analysis was used to find out which factors affect farmers' technical efficiency. The results of the study showed that farm size, household size, membership in cooperative and contract farming have a statistically significant contribution in raising production output and farmers' technical efficiency. The study recommended having programs that would focus on the significant variables to increase the technical efficiency of small-scale cacao farmers.
Thesis, Undergraduate (BS Agribusiness Economics) -- U. P. Mindanao